Adaptive mesh method applied to the thermal hydraulic program of system code with a judging criterion based on the matrix error. (October 2018) - Zhao, Xiumei; Cao, Ying; Lin, Meng; Zhang, Hao; Yang, Yanhua
Highlights: An adaptive mesh method is added in the one-dimension thermal hydraulic program. It is help to deal with the large gradient solutions with this method. A judging criterion for determining the location is proposed. Abstract: In this paper, an adaptive mesh method is described and applied to the one-dimension thermal hydraulic program in a system code for simulating the two-phase flow problems. The adaptive mesh method has been widely used to solve various engineering problems, but it is still rarely applied in existing thermal hydraulic system codes which are of great significance for reactor design and analysis. Compared with the uniform mesh, the mesh size could be adjusted automatically. It is helpful to locate the discontinuity points or deal with the large gradient solutions with this method, especially for some local phenomena that occur in phase transfer or two phase flow problems. Based on it, the computational accuracy and efficiency are improved, when solving the partial difference equations. The applicability of the adaptive mesh method in a system code is a major issue, and the first step is studying the feasibility of the adaptive mesh method in thermal hydraulic programs. In this paper, the finite volume method and the Newton-Raphson algorithm are applied in the code as the numerical method of two-fluid model. Furthermore, the code also includes heat transfer models, friction models and a flow regime map, which are important in simulating hydraulic phenomena. Depending on the algorithm, a judging criterion for determining the location where mesh refinement is needed is proposed. Three typical numerical examples are given to verify the feasibility and effectiveness of the adaptive mesh algorithm in solving the one-dimension two-phase flow problems of local phenomena and show great agreement with theoretical or experiment results.